(untitled) (Medico Legal Update, 2021)
Introduction: Indonesia has the second highest prevalence for Tuberculosis (TB) cases, with approximately two-thirds of the patients undiagnosed. Some research had investigated several aspects supporting TB new case finding a program, such as knowledge and perception while factors that affect those aspects e.g., occupational status and educational stage have not been much researched yet in Indonesia. Objective: This study aimed to identify the level of knowledge and perception regarding tuberculosis and their correlation with occupational status and educational stage. Method: An observational analytic study with the cross-sectional design conducted. A total of 51 pulmonary TB outpatients were collected and interviewed. A questionnaire was designed to obtain comprehensive information about the variables studied which consists of patient’s demographic status (age, gender, occupational status, and educational stage), along with patient knowledge and perception regarding tuberculosis. Parameters of patient understanding and perception classified as good or low based on average score. Results: The result was analyzed using Coefficient Lambda revealing a significant correlation between occupational status with a level of perception (r = 0.421, p = 0.025), while no significant correlation for the level of knowledge (p = 0.000). Spearman analysis found significant correlation between last educational stage with level of education (r = 0.569, p = 0.000), while no significant correlation for level of perception (r = 0.200, p = 0.159). Conclusion: Occupational status is an essential factor for enhancing the knowledge level of TB patient, and last educational stage is a valuable factor for intensifying level of perception of TB patient. These results will provide information for government along with healthcare workers to enhance effective health promotion program regarding knowledge and perception for tuberculosis.